Steroid hormone profiles and brain monoamine oxidase type A (MAO-A) activity of buller steers - Epp, M.P.; Blasi, Dale A.; Johnson, B.J.; Kayser, J.P.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A grazing/feedlot field study was conducted to evaluate the steroid hormone profile and brain monoamine oxidase type A (MAOA) activity of steers exhibiting characteristics attributed to the Buller Steer Syndrome in a feedlot environment. Differences of serum progesterone, testosterone, and estrogen were found in bullers at different phases of production. Brain MAO-A activity was greater in bullers than in non-bulling steers. This study suggests that MAO-A activity, under potential influence of steroidal hormones in the steer brain, may be a plausible mechanism that induces Buller Steer Syndrome.
Keywords: Beef; Steroid; Brain monoamine oxidase type A (MAO-A) activity; Buller steers